Slabs for Prefabricated Road Surfaces with the Least “Keyboard” Effect - S. I. Zinevich; A. К. Кayumov (Наука и техника, 2022)
The paper studies the issue of improving the evenness of the prefabricated concrete pavement by changing the design of the slabs from which it is assembled. Irregularities of the prefabricated pavement mainly occur at the junction of the plates and are called “keyboard” effect. The reason for the unevenness is the vertical movement of the ends of the plates relative to each other when the car passes. In order to correct this situation, the authors propose to arrange transverse ribs of rectangular cross section at the ends of the plates. Such ribs will create a reliable support at the edges of the slab, which will reduce the vertical movement of its ends. To determine the effectiveness of the use of transverse ribs, a concrete slab with dimensions of  3´6 m has been examined in the paper. The transverse rib in cross section had the shape of a rectangle with sides 20´10 cm. In order to compare the test results, a concrete slab of the same dimensions, but without transverse ribs, has been studied. Deformations and stresses of the slab under load have been determined by the finite element method using the Lira software package. Calculations have shown the effectiveness of the slabs with transverse ribs mounted on its edges. The vertical displacements of the ends of the slabs with ribs are two times less than those of the slabs without ribs, and the stresses are 2.4 times less. It is obvious that the use of concrete slabs with transverse ribs at the ends will reduce the unevenness of the prefabricated coating at the points of their mating.